2016
DOI: 10.3727/096368916x690818
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells as Treatment for Behavioral Deficits and Neuropathology in the 5xFAD Mouse Model of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is characterized by a progressive loss of memory and other cognitive disturbances. The neuropathology of AD includes the major hallmarks of toxic amyloid-β oligomer accumulation and neurofibrillary tangles, as well as increased oxidative stress, cholinergic dysfunction, synapse loss, changes in endogenous neurotrophic factors, and overall degeneration of the brain. Adult mesenchymal stem cells (MSCs) offer the potential for a readily available treatment that would be long lasting, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Though argued to contribute to cell death by affecting the DNA, previous studies by our group have observed no aberrant cell growth in response to Hoechst nuclear staining. 16 18 , 22 This stain was also determined to be adequately specific to the transplanted cells, as no efflux of the Hoechst dye to endogenous structures was observed in any of the transplanted tissue samples. Likewise, as MSCs are nonimmunogenic, no abnormal growths beyond the expected trauma-induced histopathology were observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though argued to contribute to cell death by affecting the DNA, previous studies by our group have observed no aberrant cell growth in response to Hoechst nuclear staining. 16 18 , 22 This stain was also determined to be adequately specific to the transplanted cells, as no efflux of the Hoechst dye to endogenous structures was observed in any of the transplanted tissue samples. Likewise, as MSCs are nonimmunogenic, no abnormal growths beyond the expected trauma-induced histopathology were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are obtained from tissues of mesodermal origins, can be found in fat, blood, and bone marrow, and have shown promising results in the treatment of many degenerative and traumatic conditions, including Huntington's disease, 16 Alzheimer's disease, 17 stroke, 18 and SCI. 19 These cells show properties such as low immunogenicity, secretion of trophic support factors, and the ability to differentiate into multiple lineages.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the use of SC for the transport of oncolytic agents in cancer therapies requires their active migration to the tumour site [6] . Poor to non-existent in vivo migration of surgically transplanted neural stem cells (NSC) [7] or MSC [8] reduced the grafted cells ability to reach multiple disease-affected areas of the brain. The requirement not only to migrate, but to do it as fast as possible is of special importance for oncovirolytic cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Other than differences in vascular compromise, the cell concentration could have also factored in affecting the overall survival of the VCI-subjected mice. A former group injected 2 × 10 5 MSCs suspended in 2 µL of Hank's balanced salt solution (HBSS) bilaterally into the lateral ventricles of 6-month-old 5xFAD mice [40]. The authors proposed that therapeutic benefits were enhanced when MSCs were bilaterally injected into the lateral ventricles and not the bilateral hippocampi.…”
Section: Discussionmentioning
confidence: 99%